P0322OUR EXPERIENCE IN ELECTRONIC CONSULTATION FOR REDUCING WAITING LIST AND OPTIMIZING NEPHROLOGY HEALTHCARE. (6th June 2020) - Gorriz, Jose Luis; De Ramon, Rosa; Torregrosa Maicas, Isidro; Moncho, Francesc; Garcia-Vicente, Sergio; Gimenez-Civera, Elena; D'Marco, Luis; Romero-Parra, Maria; Sanchis, Irina; Perez-Bernat, Elisa; Pérez Ys, Aurora; Juan-Garcia, Isabel; et al.
Abstract: Background and Aims: Chronic kidney disease (CKD) is recognized as a health problem in the general population; as a result, there is a growing demand for specialist services. This is especially relevant in the Spanish health system which covers the entire population free of charge. We describe our experience with new e-consultation software that allows specialists to provide clinical recommendations to primary care providers about non-subsidiary patients referred to our Nephrology Department. This system respects current protocols and is based on patient chart review without face-to-face visits, thus avoiding unnecessary time wastage in the healthcare system. Method: Our Nephrology department covers the metropolitan area of Valencia with 341, 972 citizens attended by 16 primary care centers. The Community IT software system allows all doctors (hospitals and primary care) to access the patient's medical records including laboratory, radiology, anthropometric data and treatments. A mailbox, developed as part of the Hospital General's IT system, receives all proposed referrals from primary care doctors to our department. A nephrologist then decides if the e-consultation requires an in-person visit or can be answered as a non face-to-face visit. Thus, patient's appointments are scheduled in less than one week (mean 3.8±4.5 days) and the outpatient visit in less than 14 days. The main referral criteria were: albumin/creatinine ratio> 300 mg/g, eGFR<30 ml/min/1.73 (<45 in <70 years), renal progression, resistant hypertension in CKD patients, electrolyte abnormalities and renal anemia. Patients with conditions that do not meet referral criteria are attended and given the appropriate recommendations via e-consultation. The patient is not required to present at the hospital. We describe the results of e-consultations from 1 St September 2017 to 31 st December 2019. Results: A total of 2641 consultations were submitted between September, 2017 to December, 2019 (807 in 2017, 861 in 2018 and 903 in 2019). Of these, 285 (12%) were answered as non face-to-face visit (6% of the 2017 e-consultations, 11% from 2018 and 24% from 2019). The characteristics of the 285 non face-to-face e-consultations: mean age: 68.9 ±19.5 years, female: 61.4%, diabetics: 31.2%. The main reasons for referral were: mild/low eGFR (35%), mild albuminuria (10%), administrative questions related to treatments (10%), mild hypertension (4%), mild electrolyte disturbances (2%), subacute renal dysfunction resolved (10%) (mostly NSAIDs), non-nephrology causes (mainly urological) (8%), non-renal pathology (simple renal cysts, other) (10%) and other causes (11%). The re-consult rate was 2% within the first year. Regarding patients referred with low eGFR, the mean age was 76 ± 14 years (range: 19-98), female sex: 73.9%, eGFR: 39±11 ml/min/1.73m2, serum creatinine 1.4 ± 0.4 mg/dL. Urine alb/creat ratio: 49±127 mg/g. Thirty five percent of them were between 70-79 years and 48% were> 80 years old. For those patients referred with mild albuminuria: mean age was: 57±21 years, male sex: 61%, diabetics: 31%, eGFR: 77±18 ml/min/1.73m2, serum creatinine 0.87±0.27 mg/dL. Urine alb/creat ratio: 83 ± 54 mg/g (range 33-128). There was a 17 day waiting list to attend an outpatient nephrology clinic in 2016 (previous to the initiation of the e-consultation period). On the contrary, during the study period it was 14 days in 2017 and 4 days each in both 2018 and 2019. Conclusion: Our experience shows that non-face-to-face e-consultation for patients with mild renal pathology promotes the effective management of patients who do not meet remission criteria according to established protocols. It also prevents the remission of a significant percentage of patients, reduces the waiting list and optimizes the healthcare system's resources.